2019
DOI: 10.1002/jcla.22837
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status of euthyroid adults: A cross‐sectional, multicenter study

Abstract: BackgroundIodine, an essential nutrient, is the most important trace element in thyroid hormone synthesis and maintenance of thyroid function. This study investigated the iodine nutrition status in healthy Chinese adults and assessed the relationship between urinary iodine concentration (UIC) and thyroid hormone levels.MethodsA cross‐sectional, multicenter study was conducted between October 2017 and January 2018, with 1017 adults recruited from five cities in China. All subjects underwent thyroid ultrasonogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
(30 reference statements)
6
4
0
Order By: Relevance
“…Smoking decreases the iodine level of visceral leishmaniasis patients by 12.34 mcg/l. This nding agrees with previous scholar's work [66]. This is due to the effect of smoking in disturbing the iodine metabolism [67,68].…”
Section: Discussionsupporting
confidence: 93%
“…Smoking decreases the iodine level of visceral leishmaniasis patients by 12.34 mcg/l. This nding agrees with previous scholar's work [66]. This is due to the effect of smoking in disturbing the iodine metabolism [67,68].…”
Section: Discussionsupporting
confidence: 93%
“…Smoking decreases the iodine level of visceral leishmaniasis patients by 12.34mcg/l. This nding agrees with previous scholar's work [65]. This is due to the effect of smoking in disturbing the iodine metabolism by disrupting the normal thyroid gland functions [66,67].…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, with the increasing number of patients with hypothyroidism in the population, the impact of iodine and uoride on thyroid function has become a hot issue of common concern but the research results are different [7,13,14] [15-21, 38, 39] . This study found that gender and urinary iodine are in uencing factors of TSH increase, which is consistent with the results of studies such as Vanderpump MP [12], Danchen Wang [40], and Wang D [41] Drinking water uoride is a critical in uencing factor. Some studies have found that [6,15,16,42,43] high uoride and high iodine and high uoride are related to elevated serum TSH.…”
Section: Discussionsupporting
confidence: 91%